Correlates of 2009 H1N1 influenza vaccine acceptability among parents and their adolescent children - Painter, Julia E. (Oxford University Press, 2011)
School-aged children were a priority group for receipt of the pandemic (2009) H1N1 influenza vaccine. Both parental and adolescent attitudes likely influence vaccination behaviors. Data were collected from surveys distributed to middle- and high-school students and their parents in two counties in rural Georgia. Multivariable logistic regression analyses were conducted to assess correlates of parental acceptance of H1N1 influenza vaccination for their children and adolescents’ acceptance of vaccination for themselves. Concordance analyses were conducted to assess agreement between parent–adolescent dyads regarding H1N1 influenza vaccine acceptance. Parental acceptance of H1N1 influenza vaccination for their children was associated with acceptance of the vaccine for themselves and feeling motivated by the H1N1 influenza pandemic to get a seasonal influenza vaccine for their child. Adolescents’ acceptance was associated with receipt of a seasonal influenza vaccine in the past year, fear of getting H1N1 influenza, feeling comfortable getting the vaccine and parental acceptance of H1N1 influenza vaccine. Half (50%) of parent–adolescent pairs included both a parent and child who expressed H1N1 influenza vaccine acceptance, and 19% of pairs would not accept the vaccine. This research highlights the need for interventions that target factors associated with H1N1 influenza vaccine acceptance among both parents and adolescents.